Navigating large-volume subcutaneous injections of biopharmaceuticals: a systematic review of clinical pipelines and approved products - Philip Green; Andreas Schneider; Jakob Lange (mAbs)
Subcutaneous (SC) administration is transforming the delivery of biopharmaceuticals, facilitating care in a variety of healthcare settings, including home self-treatment. Large-volume single SC doses have gained attention for their potential to expand therapeutic applications and improve long-term, patient-centric dosing regimens, often at a reduced SC injection frequency. However, a systematic understanding of dose volumes and frequencies for large-volume (>2.0 mL) SC biopharmaceuticals (LVSCs) is lacking. Accordingly, this study systematically reviewed clinical-stage and approved intravenous (IV) and SC biopharmaceuticals, identifying 182 LVSCs – predominantly monoclonal or bispecific antibodies – which correspond to approximately 15% of all IV and SC biopharmaceuticals. These LVSCs are designed to target cancer and a range of non-cancer chronic disease states, including autoimmune, neurological, and cardiovascular diseases. Results show that anti-cancer LVSCs (n = 75) typically require 5.0 to 20.0 mL doses every three weeks and are administered by healthcare professionals. In contrast, non-cancer LVSCs (n = 107), which are typically self-administered monthly, show more significant dosing variability, with < 5.0 mL being the predominant volume range. Furthermore, the study identified a substantial clinical pipeline of potential LVSCs, many of which are being injected at increasingly lower dosing frequencies, suggesting significant future growth in this area. Most non-cancer LVSCs are currently undergoing clinical trials via the SC route, whereas the majority of the cancer LVSCs are being administered IV and require transition to the SC route. These findings highlight the importance of developing large-volume drug delivery systems and novel formulations to reduce injection volumes. The analysis provides valuable guidance for new product development, as well as for marketing and commercialization strategies in the rapidly evolving LVSC landscape.